Book Review: Rethinking Heritage for Sustainable Development by Sophia Labadi - Jordana Maguire (EXARC Journal)
The concept of heritage has long been associated with the preservation and commemoration of our collective cultural legacy. In the context of development, however, heritage takes on a multifaceted role, encompassing not only the preservation of historical artefacts and traditions but also their active integration into processes that drive socioeconomic progress.